1984
DOI: 10.1083/jcb.99.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Dualistic nature of adhesive protein function: fibronectin and its biologically active peptide fragments can autoinhibit fibronectin function.

Abstract: Fibronectin and certain polypeptide regions of this adhesive glycoprotein mediate cell attachment and spreading on various substrates. We explored the theoretical prediction that this adhesive protein could become a competitive inhibitor of fibronectin-mediated processes if present in solution at appropriately high concentrations. Fibronectin function was inhibited by purified plasma fibronectin at 5-10 mg/ml, by a 75,000-dalton cell-interaction fragment of the protein at 0.5-1 mg/ml, and even by two synthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
196
1

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 440 publications
(205 citation statements)
references
References 29 publications
8
196
1
Order By: Relevance
“…Adherent cells then slowly (typically within hours) spread over the surface, depending on compatibility with the surface, expressing a strong 'biological component of adhesion' [38] that includes secretion of extracellular matrix (ECM) and results in the flattening of cells on the substratum [2] (spreadcell length is about 3-10 times height [9]). Needless to say, (protein) composition of the fluid phase can greatly affect the entire cell adhesion process [31,33,[55][56][57][58][59]. Thus, it is apparent that the short-term (<3 days) cell adhesion/proliferation process spans a broad range of time and length scales.…”
Section: Cell Attachment and Proliferation Kineticsmentioning
confidence: 99%
“…Adherent cells then slowly (typically within hours) spread over the surface, depending on compatibility with the surface, expressing a strong 'biological component of adhesion' [38] that includes secretion of extracellular matrix (ECM) and results in the flattening of cells on the substratum [2] (spreadcell length is about 3-10 times height [9]). Needless to say, (protein) composition of the fluid phase can greatly affect the entire cell adhesion process [31,33,[55][56][57][58][59]. Thus, it is apparent that the short-term (<3 days) cell adhesion/proliferation process spans a broad range of time and length scales.…”
Section: Cell Attachment and Proliferation Kineticsmentioning
confidence: 99%
“…The tripeptide RGD motif is a major recognition site for integrins within some ligands, such as fibronectin or fibrinogen (11,12). However, although ␣2␤1 integrin contains an RGD-binding site, their natural ligands, collagens type I and type IV, used a different binding sequence (GFOGER) (13) and are classified as RGD-independent ligands (14,15).…”
mentioning
confidence: 99%
“…Common or characteristic core sequences in cell adhesion molecules such as fibronectin (Kornblihtt et al, 1985), vitronectin (Suzuki et al, 1985) and laminin Sasaki have been found to contribute to cell adhesion, and to the spread or migration of cells (Yamada & Kennedy, 1984;McCarthy & Furcht, 1984;Humphries et al, 1986). It has been shown that the domain of fibronectin in cellular recognition is carried by an ArgGly-Asp-Ser (RGDS) sequence.…”
mentioning
confidence: 99%
“…The RGD sequence exists commonly in many adhesion molecules (Pierschbacher & Ruoslahti, 1982. RGD-containing peptides have been shown to promote cell adhesive capability after their surface immobilisation, and to inhibit cell adhesion to fibronectin when added freely in solution (Yamada & Kennedy, 1984Akiyama & Yamada, 1985).…”
mentioning
confidence: 99%